Redefining Risk : Indian Sterling Bank’s Journey to Mitigate Concentration Risk - Mainrai, Girish; Mohania, Sarvesh (Indian Journal of Finance, 2023)
Purpose : The present case study highlighted the impact of concentration risk on the performance of banks. This case focused on the functioning and various challenges faced by a hypothetical private sector bank, that is, Indian Sterling Bank, on account of overexposure to a specific industry. It highlighted the importance of risk assessment and continuous learning in managing risks. Findings : Banks are exposed to various types of risk like credit, market, operational, liquidity, and earning risk, to name a few. Overexposure to a particular sector exposed a bank to concentration risk. Any adverse conditions like demand fluctuation, policy changes, and changes in customer preferences affect the earnings and, ultimately, the viability of an industry. This, in turn, affects the banks which have taken exposure to that industry. Practical Implications : Banks are exposed to various types of risks, which could impact not only their earnings but also their survival. This case study highlighted the importance of proactive risk management and the potential consequences of excessive concentration in a specific sector. The identification of concentration risk within the technology sector for Indian Sterling Bank underscored the critical importance of proactive risk management strategies. Banks should continuously monitor industry trends, economic indicators, and regulatory developments to anticipate potential risks. Implementing stringent risk assessment practices, stress testing, and scenario analysis would enable the bank to effectively identify, assess, and manage concentration risk, ensuring sustained financial stability and safeguarding against adverse sector-related events. Originality : This case study highlighted the importance of risk assessment and continuous learning in managing risks effectively and safeguarding a bank’s financial stability.